Cell Lysis and Detoxification of Cyanotoxins Using a Novel Combination of Microbubble Generation and Plasma Microreactor Technology for Ozonation - Pandhal, Jagroop; Siswanto, Anggun; Kuvshinov, Dmitriy; Zimmerman, William B.; Lawton, Linda; Edwards, Christine (Frontiers in Microbiology, 2018)
There has been a steady rise in the incidences of algal blooms globally, and worryingly, there is increasing evidence that changes in the global climate are leading to a shift towards cyanobacterial blooms. Many cyanobacterial genera are harmful, producing several potent toxins, including microcystins, for which there are over 90 described analogues. There are a wide range of negative effects associated with these toxins including gastroenteritis, cytotoxicity, hepatotoxicity and neurotoxicity. Although a variety of oxidation based treatment methods have been described, ozonation and advanced oxidation are acknowledged as most effective as they readily oxidise microcystins to non-toxic degradation products. However, most ozonation technologies have challenges for scale up including high costs and sub-optimum efficiencies, hence, a low cost and scalable ozonation technology is needed. Here we designed a low temperature plasma dielectric barrier discharge reactor with an incorporated fluidic oscillator for microbubble delivery of ozone. Both technologies have the potential to drastically reduce the costs of ozonation at scale. Mass spectrometry analysis revealed very rapid (<2 min) destruction of two pure microcystins (MC-LR and MC-RR), together with removal of by-products even at low flow rate 1 L min-1 where bubble size was 0.56-0.6 mm and the ozone concentration within the liquid was 20 ppm. Toxicity levels were calculated through protein phosphatase inhibition assays and indicated loss of toxicity as well as confirming the by-products were also non-toxic. Finally, treatment of whole Microcystis aeruginosa cells showed that even at these very low ozone levels, cells can be killed and toxins (MC-LR and Desmethyl MC-LR) removed. Little change was observed in the first 20 minutes of treatment followed by rapid increase in extracellular toxins, indicating cell lysis, with most significant release at the higher 3 L min-1 flow rate compared to 1 L min-1. This lab-scale investigation demonstrates the potential of the novel plasma micro reactor with applications for in situ treatment of harmful algal blooms and cyanotoxins.